Network-Level Optimization for Volt/Var Control in Unbalanced Electric Power Distribution Systems - Jha, Rahul Ranjan (ProQuest Dissertations & Theses, 2020)
The distribution optimal power flow (D-OPF) models have gained attention in recent years to optimally operate a centrally managed distribution grid. The key requirement of the D-OPF is to obtain a feasible solution for the real-time operation in the distribution system. Towards this goal, following are the major contributions in this dissertation. First, for a distribution system, all the controllable devices are required to be known in advance for optimal operation. Next, to develop an algorithm, each component in the system are modelled with the same sets of variables. In this dissertation, we developed a mathematical model for capacitor banks, voltage regulators, loads and generators wrt to branch flow model based power flow equations. Next, D-OPF algorithm is developed for volt-var optimization (VVO) with conservation voltage reduction (CVR) for a distribution system. Second, we investigate that the D-OPF algorithm obtained by solving nonlinear programming is not scalable. Hence, we are required to develop an algorithm which can solve D-OPF problem faster, which can be implemented for the real-world problem. In this regard, we have developed iterative algorithm based an approximation and relaxation of the nonlinear power flow equations. It has been investigated that the proposed iterative algorithm is scalable and are able to obtain a feasible solution.Third, mostly the D-OPF algorithm is solved at the centralized location and solved in discrete time interval (5 or 15 min). Due to large scale deployment of distributed energy resources (DERs) specially roof-top PVs, there is fluctuation in power production within 5 or 15 min time interval. This hinders the optimal operation of the system and deteriorates the life-cycle of the legacy devices installed in the system. Here, we developed local control methods which works in coordination of the centralized control. The combined control method is able to reduce the power consumption from a feeder as well as to maintain power quality. Fourth, we integrated a volt-var optimization (VVO) application on an ADMS environment using the GridAPPS-D platform. The successful deployment of the VVO application on the GridAPPS-D platform provides a proof-of-concept for the adoption of advanced applications to support future distribution systems.